2019
DOI: 10.1186/s12917-019-2118-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of allogeneic freeze-dried platelet lysate in cartilage exposed to interleukin 1-β in vitro

Abstract: BackgroundPlatelet-rich plasma (PRP) as well as other platelet-derived products have been used as a potential disease-modifying treatment for musculoskeletal diseases, such as osteoarthritis (OA). The restorative properties of such products rely mainly on the high concentrations of growth factors, demonstrating encouraging results experimentally and clinically. Yet, the autologous blood-derived nature of the PRP product lead to limitations that precludes it’s widespread use. The main limitations for PRP use ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…This is the first study to confirm that al-PRP has an equivalent effectiveness and safety to accelerate wound healing of DLEUs. Furthermore, the present study was supported by a basic study of cartilage culture, in which the results suggested that allogeneic freeze-dried platelet lysate presented equivalent effects compared to frozen autologous platelet lysate 50 .…”
Section: Discussionsupporting
confidence: 67%
“…This is the first study to confirm that al-PRP has an equivalent effectiveness and safety to accelerate wound healing of DLEUs. Furthermore, the present study was supported by a basic study of cartilage culture, in which the results suggested that allogeneic freeze-dried platelet lysate presented equivalent effects compared to frozen autologous platelet lysate 50 .…”
Section: Discussionsupporting
confidence: 67%
“…Finally, the allogeneic CGF could be used in patients in whom CGF cannot be extracted due to medical conditions. Some studies have reported that freeze-dried platelets and platelet lysate can be used for cell culture and tissue healing [12,13]. CGF is a concentrate of blood platelets, and freeze-drying could be used for CGFs, which could expand the scope of use of CGF for healing applications.…”
Section: Introductionmentioning
confidence: 99%
“…The latter was achieved through a reduction in common inflammatory molecular pathways, such as NF-kB activation and nitric oxide (NO) synthesis. Similarly, dose-related chondroprotective actions of PRP, without differences between FD-PRP compared to fresh-frozen PRP, were found in equine cartilage cultures [51]. In a similar way, standardized human PRP powder induced a dose-and time-response relationship in human chondrocyte proliferation and metabolic activity [52].…”
Section: Musculoskeletal Applicationsmentioning
confidence: 82%